(x+1)(x-2)=(x-1)(x-1)

Simple and best practice solution for (x+1)(x-2)=(x-1)(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)(x-2)=(x-1)(x-1) equation:


Simplifying
(x + 1)(x + -2) = (x + -1)(x + -1)

Reorder the terms:
(1 + x)(x + -2) = (x + -1)(x + -1)

Reorder the terms:
(1 + x)(-2 + x) = (x + -1)(x + -1)

Multiply (1 + x) * (-2 + x)
(1(-2 + x) + x(-2 + x)) = (x + -1)(x + -1)
((-2 * 1 + x * 1) + x(-2 + x)) = (x + -1)(x + -1)
((-2 + 1x) + x(-2 + x)) = (x + -1)(x + -1)
(-2 + 1x + (-2 * x + x * x)) = (x + -1)(x + -1)
(-2 + 1x + (-2x + x2)) = (x + -1)(x + -1)

Combine like terms: 1x + -2x = -1x
(-2 + -1x + x2) = (x + -1)(x + -1)

Reorder the terms:
-2 + -1x + x2 = (-1 + x)(x + -1)

Reorder the terms:
-2 + -1x + x2 = (-1 + x)(-1 + x)

Multiply (-1 + x) * (-1 + x)
-2 + -1x + x2 = (-1(-1 + x) + x(-1 + x))
-2 + -1x + x2 = ((-1 * -1 + x * -1) + x(-1 + x))
-2 + -1x + x2 = ((1 + -1x) + x(-1 + x))
-2 + -1x + x2 = (1 + -1x + (-1 * x + x * x))
-2 + -1x + x2 = (1 + -1x + (-1x + x2))

Combine like terms: -1x + -1x = -2x
-2 + -1x + x2 = (1 + -2x + x2)

Add '-1x2' to each side of the equation.
-2 + -1x + x2 + -1x2 = 1 + -2x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-2 + -1x + 0 = 1 + -2x + x2 + -1x2
-2 + -1x = 1 + -2x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-2 + -1x = 1 + -2x + 0
-2 + -1x = 1 + -2x

Solving
-2 + -1x = 1 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-2 + -1x + 2x = 1 + -2x + 2x

Combine like terms: -1x + 2x = 1x
-2 + 1x = 1 + -2x + 2x

Combine like terms: -2x + 2x = 0
-2 + 1x = 1 + 0
-2 + 1x = 1

Add '2' to each side of the equation.
-2 + 2 + 1x = 1 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 1 + 2
1x = 1 + 2

Combine like terms: 1 + 2 = 3
1x = 3

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 | | 11x-12=13x-20 | | 6x+3y=153 | | x+y=1.23 | | 5-x=32 | | 2x+15=13x+1 | | 10x+(12-x)=9x+12 | | 5x-1=10x-17 | | 19x+2=3x+14 | | 10/x=6.3681 | | 4.6/y=44.16 | | -32*Y=-22336 | | 10y+15x=5 | | (12-x)+x=12+36 | | (12-x)+x=12 | | 143=6x+17 | | 5(2y+4)=24 | | 8x+7=7x-3 | | W-(-322)=-728 | | 10x^5/2x^2 | | 4a+17=a+13 |

Equations solver categories